Estudo da luminescência persistente no composto (Sr1-xCax)1-abAl2O4: Eu2+aTR3+b - Lima, Amanda Santana (2025)
Persistent luminescence is the optical phenomenon in which the material continues to emit light, with appreciable intensity, even after the excitation has ceased. This study investigated powders of the compounds (Sr1-xCax)1-a-bcAl2O4:Eu2+ aDy3+ bNd3+ c, synthesized by the polymeric precursor method, followed by pre-calcination and thermal treatment in a vacuum furnace. X-ray diffraction (XRD) results showed the phase transition from SrAl₂O₄ to CaAl₂O₄ with the increase of Ca²⁺, resulting in a contraction of the crystal lattice. Photoluminescence measurements exhibited a broad emission band from 400 to 600 nm, attributed to the 4f⁶5d¹→4f⁷ transition of Eu²⁺, varying from green to blue as the Ca concentration increases. The lifetime curves indicated both short and long duration decay processes. The initial intensity and luminescent decay time varied, being higher in samples with a greater proportion of Ca²⁺. Radioluminescent characterization showed two main bands centered at 450 nm and 535 nm, attributed to the 5d → 4f transitions of Eu²⁺, sensitive to the crystal environment of the ion. Transitions 5D₀→⁷F₂ (605, 630 nm) and 5D₀→⁷F₀ (585 nm) characteristics of Eu³+ were also identified. It was concluded that the Sr/Ca ratio and the concentration of dopants are fundamental to adjust the luminescent properties, allowing applications in safety, lighting, and advanced devices.